Outpatient Patient Satisfaction With Radiology Services at Puri Husada Hospital, Tembilahan - Malik, Yogi Septian; Ardeline, Mela; Eqiu Al Kahfi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Hospital is a facility in the health sector that provides services in both the medical and non-medical fields in order to improve the degree of public health. Good service in the medical field, especially radiology services, can improve health status and community satisfaction. This study aims to determine the relationship between outpatient satisfaction with radiology services at Puri Husada Tembilahan Hospital. This type of research is analytic to see the relationship between one variable and another with a cross sectional approach. The number of samples was 200 respondents determined by incidental sampling technique. The statistical test used is the Chi Square Test. The results showed that the p value was 0.000. So it can be concluded that there is a relationship between outpatient satisfaction with radiology services at Puri Husada Tembilahan Hospital. It is expected that all officers at the Radiology Installation of the Puri Husada Tembilahan General Regional Hospital to maintain the level of patient satisfaction with the quality of service at the Puri Husada Tembilahan General Regional Hospital.